(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
The growing concern for sustainability highlights the importance of environmental management in companies. For this reason, the adoption of circular economy models (circularity) and the development of eco-innovations represent sources of competitive advantages that contribute to meeting short and long-term environmental goals. This research deepens into the drivers of circularity and eco-innovation through the study of the relationship between each of these practices and the type of business ownership, whether family or non-family. Based on socio-emotional wealth theory and its explanation of why family firms have a greater interest in non-financial aspects, we propose that family firms are more circular and eco-innovative than non-family firms. To test our hypothesis, we use data from the Flash Eurobarometer 486 on SMEs, start-ups, scale-ups and entrepreneurship. The results lead us not to reject the proposed hypothesis. Thus, we observe that the type of ownership of the firms is a key organizational factor when environmental measures are implemented. Specifically, we conclude that family businesses have a higher propensity towards environmental development.